Thinking about Certainty and Tolerance with Michel Eyquem de Montaigne - Diatka, Cyril; Ligus, Jan (Communications - Scientific Letters of the University of Zilina, 2016)
Michel Montaigne's thinking, though primarily relevant to and based upon his own historical context, exhibits unique traits and provides inspiration to current socio-political, ethical, and philosophical discourse. This study deals with Montaigne's peculiar epistemological skepticism, arguing that, if adequately understood, it may prove an important factor in human striving for tolerance. With his emphasis on the emancipation (and separation) of politics from religion and positing the will of an individual human person as the determining factor in the development of human societies, Montaigne brings a significant contribution.
Keywords: Michel Montaigne; skepticism; tolerance; epistemology; certainty